Komunikacinių mokėjimų struktūra ir turinys - Grebliauskienė , Beata (Information & Media, 1997)
This article deals with the structure and content of communicational skills. On the basis of analysis of the concepts and classifications of the skills there are suggested the criteria of analysis and description of the specific skills. According to those criteria communicational skills are defined as ability to successful manage (create) information and to exchange an aspiration for common understanding. Specifics of the communication process allowess to identificate operational-technical and gnostic abilities. On the basis of literature analysis the following gnostic skills are pointed out: the skill to use the system of signs (language) and the skill to organize communication based on the principle of dialogue. Gnostic ability is considered as foundation of the communicational ability. It serves as a basis for two-type operational-technical skills - acceptive and expressive. The complex of gnostic and operational-technical skills form systemic, incomplete  communicational ability.
Keywords: -